Toward a Theory of the Evolution of Fair Play - Schank, Jeffrey C.; Burghardt, Gordon M.; Pellis, Sergio M. (Frontiers in Psychology, 2018)
Juvenile animals of many species engage in social play, but its functional significance is not well understood. This is especially true for a type of social play called fair play. Social play often involves behavioral patterns similar to adult behaviors (e.g., fighting, mating, and predatory activities), but young animals often engage in fair play behaviors such as role-reversals and self-handicapping, which raises the evolutionary problem of why fair play exists. A long-held working hypothesis, tracing back to the 19th century, is that social play provides contexts in which adult social skills needed for adulthood can be learned or, at least, refined. On this hypothesis, fair play may have evolved for adults to acquire skills for behaving fairly in the sense of equitable distribution of resources or treatment of others. We investigated the evolution of fair play using an evolutionary agent-based model of populations of social agents that learn adult fair behavior by engaging in fair play as juveniles. In our model, adults produce offspring by accumulating resources over time through foraging. Adults can either behave selfishly by keeping the resources they forage or they can pool them, subsequently dividing the pooled resources after each round of foraging. We found that fairness as equitability was beneficial especially when resources were large but difficult to obtain and led to the evolution of fair play. We conclude by discussing the implications of this model, for developing more rigorous theory on the evolution of social play, and future directions for theory development by modeling the evolution of play.